Soliditas aquaeductus ... servetur. Controllo e amministrazione degli acquedotti nell’Italia ostrogota - Marano, Yuri A. (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 2021)
Abstract Written and archaeological evidence from Ostrogothic Italy offers the opportunity to investigate how a late antique society coped with hydraulic problems. Although stretching across a few decades (from the establishment of Theoderic’s power over Italy in AD 493 and the end of the Gothic war in AD 555), the Ostrogothic period is marked by social, economic, political and cultural transformations which affected the management of water. Ostrogothic authorities held control over aqueducts and the water supply following earlier administrative and legal tradition. Though there is evidence for private misappropriation of part of public aqueducts’ water, the main function of aqueducts - to make ample supplies of water available to entire communities - was generally achieved. At the same time, it is undeniable that they had to cope with irreversible trends, whose impact was magnified by major historical events such as the Gothic war.